Kinetics investigation of changing the oil film thickness depending on the material of friction pairs - Дмитриченко, Микола Федорович; Білякович, Олег Миколайович; Глухонець, Андрій Олексійович; Міняйло, Костянтин Миколайович (Technology audit and production reserves, 2015)
This article discusses the problems of dependence of changes of the effective viscosity of the ATF synthetic gear oil depending on the material of friction pairs. The aim of this article is to investigate the factors influencing the carrying capacity of the oil film. Tests were conducted on СМЦ-2 friction machine on the rollers, which are made of 40X steel (HRC=40) and ШХ-15 steel (HRC=60) at loads σmax=450, 570 and 680 MPa. Starting bulk oil temperature was 18 °C. The thickness of the lubricating layer was measured by the fall of a normal glow discharge. It was proved that a decrease in the hardness of contact surfaces leads to dominance in contact elastohydrodynamic factors of growth of the total thickness of the lubricating layer at the pushing, which is associated with a decrease in pressure-viscosity oil coefficient correlated growing influence of the dimensionless parameter of the material. The research results can be used in laboratories, manufacturers of lubricants in forming or improving their composition. From the kinetics analysis of formation of the lubricant layer at the contact surfaces of different hardness we can conclude that on the carrying capacity of the oil film in contact affect rheological characteristics of the oil and the dimensionless parameter of the material which depends on pressure-viscosity oil coefficient.